Participation in hybrid sketching - Berg, Arild (FormAkademisk, 2018)
In the age of digitalisation, the role of the sketch has taken new forms, but it still works as a mediator between people who work to create something together. There is, however, a lack of knowledge about how the sketch can be used as a strategy to increase participation and collaboration in creative processes. Participation in various types of sketching was explored through a case study with a participatory design approach in a public art project for a health centre. The study demonstrated how hybrid materialisations of a sketch have value as a communicative medium. Essential concepts emerged from collaborative learning in fieldwork that created shared understanding based on drawing experiments. The concepts contribute to a typology of hybrid sketches used as creativity skills in the expanded field of art. Keywords: Collaborative learning, participatory design, artistic research, drawing in the expanded field, management of creative processes